Penerapan Model Pembelajaran Carousel Feedback dalam Meningkatkan Motivasi dan Hasil Belajar - Anselmus Mema; Benedikta Boleng (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to improve the motivation and learning outcomes of Social Studies students in grade IV SDI Watujara Ende. This research includes Classroom Action Research (CAR) by applying two cycles. Data collection techniques using observation techniques, questionnaires, tests, interviews, documentation, and field notes. The collected data were analyzed descriptively qualitative and quantitative descriptive. The results showed that the carousel feedback learning model can improve motivation and learning outcomes. This can be seen from the increase in the percentage of students' motivation to achieve high and very high categories, which is 75% in the first cycle to 83% in the second cycle. Student learning outcomes have also increased, seen from the percentage of classical completeness that is 75% in the first cycle to 92% in the second cycle. Conclusions, that after applying carousel feedback learning can increase motivation and social studies learning outcomes of students. Keywords: Carousel Feedback, Motivation, Learning Outcomes